TRANSRADIAL PRIMARY PCI OF AN ANOMALOUS LAD ORIGINATING FROM THE OPPOSITE SINUS PRESENTING AS STEMI - Romero, Jorge Ramirez; Tschannen, William; Wermers, Jason P.; Ahmad, Sarah Aftab; Khalid, Nauman (Journal of Ayub Medical College Abbottabad, 2022)
ST-segment elevation myocardial infarction (STEMI) is a rare presentation in patients with anomalous coronary arteries. Among these patients, identification of the culprit lesion remains challenging. Furthermore, the default transradial approach advocated by the guidelines and professional societies, especially for acute coronary syndromes may pose technical challenges for the interventionalists.